Waste heat recovery and water-saving modification for a water-cooled gas-steam combined cycle cogeneration system with absorption heat pump. (15th January 2019) - Zhang, Hongsheng; Zhao, Hongbin; Li, Zhenlin
Highlights: Proposed a new method to achieve waste heat recovery and water saving. Verified that waste heat recovery can offset property reduction of air-cooled mode. Both energy and exergy analysis are conducted to identify advantages of new system. Abstract: A new air-cooled gas-steam combined cycle cogeneration system with absorption heat pump for recovering waste heat from exhausted steam of the steam turbine to achieve double effects of waste heat recovery and water saving is proposed based on a conventional water-cooled gas-steam combined cycle cogeneration system in the paper. The property criteria variation is analyzed before and after modification. In addition, the exergy analyses of primary equipments are carried out based upon the exergy analysis theory. The results demonstrate that the net generating power is approximately increased by 11, 082 kW, equivalent coal consumption is reduced by 2.71 g/kWh, the net overall thermal efficiency is improved by 0.91% with 334, 245 kW heating load at 100% load of the gas turbine in the modified system. Besides, the overall exergy loss is decreased by 6448 kW and exergy efficiency is improved by 0.98%. The overall property of the whole system is improved. The results show that the property reduction caused by air-cooling modification can be made up by the property improvement due to waste heat recovery. Moreover, the cooling circulating water can be saved by 1196.34 kg/s. The presented measure can not only improve performance of the system but also simultaneously achieve energy and water saving on the premise of satisfying user needs, which has a wide application potential in the water-shortage regions.